Fracture of Nano and Engineering Materials and Structures Proceedings of the 16th European Conference of Fracture, Alexandroupolis, Greece, July 3-7, 2006 - Gdoutos, E.E.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
This volume contains two-page abstracts of the 698 papers presented at the “16th European Conference of Fracture,” (ECF16) held in Alexandroupolis, Greece, July 3-7, 2006. The accompanying CD attached at the back cover of the book contains the full length papers. The abstracts of the fifteen plenary lectures are included in the beginning of the book. The remaining 683 abstracts are arranged in 25 tracks and 35 special symposia/sessions with 303 and 380 abstracts, respectively. The papers of the tracks have been contributed from open call, while the papers of the symposia/sessions have been solicited by the respective organizers. Both tracks and symposia/sessions fall into two categories, namely, fracture of nanomaterials and structures and engineering materials and structures with 88 and 595 papers, respectively. Started in 1976, the European Conference of Fracture (ECF) takes place every two years in a European country. Its scope is to promote world-wide cooperation among scientists and engineers concerned with fracture and fatigue of solids. ECF16 was under the auspices of the European Structural Integrity Society (ESIS) and was sponsored by the American Society of Testing and Materials, the British Society for Stain Measurement, the Society of Experimental Mechanics, the Italian Society for Experimental Mechanics, and the Japanese Society of Mechanical Engineers. ECF16 focused in all aspects of structural integrity with the objective of improving the safety and performance of engineering structures, components, systems and their associated materials.
Editor’s Preface. Organizing Committees -- ECF16 Tracks. ECF16 Special Symposia/Sessions -- A. Invited Papers: Deformation and Fracture at the Micron and Nano Scales. Statistical Mechanics of Safety Factors and Size Effect in Quasibrittle Fracture. Nanoreliability – Fracture Mechanics on the Way from Micro to Nano. Fracture Mechanics and Complexity Sciences. Failure of Composite Materials. Interactions of Constrained Flow and Size Scale on Mechanical Behavior. Space Shuttle Columbia Post-Accident Analysis and Investigation. The Role of Adhesion and Fracture on the Performance of Nanostructured Films. Assessment of Weldment Specimens Containing Residual Stress. MEMS: Recent Advances and Current Challenges. Fracture, Aging and Disease in Bone and Teeth. Laboratory Earthquakes. A Historical Retrospective of the Beginnings of Brittle Fracture Mechanics The Period 1907-1947. Dynamic Crack Propagation in Particle Reinforced Nanocomposites and Graded Materials. Spatial and Temporal Scaling Affected by System Inhomogeneity: Atomic, Microscopic and Macroscopic -- B. Tracks. B1. Nanomaterials and Nanostructures B2. Engineering Materials and Structures -- C. Special Symposia/Sessions Cl. Nanomaterials and Nanostructures. C2. Engineering Materials and Structures. Author Index.
Keywords: Mechanics; Mechanics, Applied; Solid Mechanics